Use of Iatrogenic Lipid Emulsion and Subsequent Plasmapheresis for the Treatment of Amitriptyline Overdose - Ryan C. Laffin; Ashley M. Cunningham; Sean A. Fitzgerald; Donald A. Wiebe; Jeffrey A. Wells; Janice Robin Linzell; William Nicholas Rose (Case Reports in Critical Care)
Plasmapheresis for the treatment of hypertriglyceridemia is relatively uncommon and mostly reported either in patients experiencing hypertriglyceridemia-induced acute pancreatitis or patients with therapy-resistant familial hypercholesterolemia. Standard therapies for hypertriglyceridemia include dietary modification and lipid-lowering medication. For severe hypertriglyceridemia, the risk of pancreatitis increases significantly as triglyceride levels increase above 1000 mg/dL, and current therapies are unable to reduce triglyceride levels rapidly enough. Here, we report a case of a 48-year-old male patient who presented to the emergency department due to an amitriptyline overdose. In addition to being started on IV sodium bicarbonate therapy, an intravenous 20% fat emulsion bolus at 1.5 mL/kg was administered followed by 0.25 mL/kg/min infusion for 4 hours as a strategy to absorb lipophilic amitriptyline. Two days posttreatment, he was noted to have substantial hypertriglyceridemia (serum triglycerides: 6,475 mg/dL). His amylase was within the normal range at 37 U/L (reference range: 20-100 U/L), his lipase was low at 40 U/L (reference range: 75-390 U/L), and he was without evidence of any clinical sequelae secondary to hypertriglyceridemia (e.g., pancreatitis). Due to the severity of his hypertriglyceridemia, plasmapheresis was initiated urgently for rapid reduction in serum triglyceride levels to prevent pancreatitis and end-organ damage. He underwent a 1-plasma volume exchange with 5% albumin as the replacement fluid. This reduced his triglyceride levels to 185 mg/dL (reference range: 3-149 mg/dL). His symptoms secondary to his amitriptyline overdose were also resolved. Here, we report a 2-step process of intravenous lipid emulsion followed by plasmapheresis for amitriptyline overdose.